PENGARUH IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) TERHADAP PRESTASI BELAJAR SISWA PADA SEKOLAHDASAR ISLAM TERPADU DI MAKASSAR - Thahir, Irmawati (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2018)
Effect of Implementation of School-Base Management on Student Achievement in Intergrated Islamic Primary School in Makassar . This research is based on compability between the concept of intergrated schools with SBM, the number of applicants on alleged SD IT is increasing because good management so that the achievements of their students are well too. This type of research is descriptive quantitative method used is survey. Quantitative method analysis descriptive statistics and inferential analysis, with regression test. The results showed that the implementation of SBM from management aspects of the curriculum, educators and educational management in SDIT in Makassar has been done regularly and independently. The respondents’ answers show trends in the high category. This study also found that: first, there was an impact of implementing SBM from the aspect of curriculum, educatos and educational management, and students in Makassar; second, there was a positive effect of the SBM implementation from the aspect of educators and educational management toward the students achievement of SDIT students in Makassar; third, there was a positive effect of the SBM implementation from the aspects of students management on students achievement of students of SDIT in Makassar.